2022
DOI: 10.3390/ma15134404
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Wood Pellets in the Production of High Quality Biocarbon Materials

Abstract: Biomass is one of the most important sources of renewable energy. One of the most widely used biomass biofuels is wood pellets. It is an economical, homogeneous and easy-to-use raw material. Biomass is used to generate low-emission energy utilizing the pyrolysis process. Pyrolysis allows for higher energy efficiency with the use of commonly available substrates. This thesis presents the results of research on the possibility of using the pyrolysis process to produce high-energy biocarbons from wood pellets. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
2
1
0
Order By: Relevance
“…The analyses showed no content of total nitrogen in the samples assessed, and the processes of pyrolysis did not produce any change in this parameter. Similar conclusions were reported by Yuan et al, who investigated materials obtained from sewage sludge [48], and by Saletnik et al, who did not find a relationship between pyrolysis and changes in this parameter in biochar produced from pellets [64]. In the case of pyrolysis conducted at 400-500 • C for a duration of 5-15 min, a significant increase in carbon contents was observed in the samples, with the highest value of 63.16% obtained as a result of pyrolysis conducted at a temperature of 500 • C for a duration of 15 min.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The analyses showed no content of total nitrogen in the samples assessed, and the processes of pyrolysis did not produce any change in this parameter. Similar conclusions were reported by Yuan et al, who investigated materials obtained from sewage sludge [48], and by Saletnik et al, who did not find a relationship between pyrolysis and changes in this parameter in biochar produced from pellets [64]. In the case of pyrolysis conducted at 400-500 • C for a duration of 5-15 min, a significant increase in carbon contents was observed in the samples, with the highest value of 63.16% obtained as a result of pyrolysis conducted at a temperature of 500 • C for a duration of 15 min.…”
Section: Discussionsupporting
confidence: 89%
“…The best values of this parameter were also observed in the case of pyrolysis conducted at 500 • C for a duration of 15 min. Similar results were reported by Saletnik et al (2022) [64] in a study assessing such materials as wood, bark, brushwood, leaves and acorns subjected to pyrolysis to produce biochar. The authors observed that the changes in the contents of volatile substances were related to the pyrolysis method applied [48].…”
Section: Discussionsupporting
confidence: 89%
“…Saletnik et al classified the thermally unprocessed oak, coniferous pellets and their mixture, as well as the thermally processed forms obtained from them, into the first class of dust explosion hazard (St1)—a material not susceptible to explosiveness. Scientists noticed in-crease in this parameter for the obtained biocarbons with an increase of the temperature range and the duration of the pyrolysis process [ 144 ]. The present study shows that modifications of raw biomass required for the production of fuels with better quality parameters do not in-crease the risk of explosion.…”
Section: Resultsmentioning
confidence: 99%
“…Wood waste, including the forest waste (wood, branches, bark and sawdust), accounts for a significant proportion of wood industry waste. However, the plant biomass is quite difficult to use as a fuel and requires proper treatment because this is a heterogeneous, contaminated material, often damp and with a low energy potential (Saletnik et al, 2022). Traditionally, wood biomass was used as a fuel in energy processes, however, through innovative approaches, wood waste can be turned into a valuable resource, not only reducing waste, but also producing biochar, a greatly efficient material with adsorption properties, commonly used for the environmental management applications that include soil remediation (Ding et al, 2016;Bianco et al, 2021), carbon sequestration (Lal, 2004;Woolf et al, 2010;Tenenbaum, 2013) or adsorption of heavy metals and other impurities, and many others (Kookana, 2010;Mohan et al, 2014;Liang et al, 2006;Chen and Pilla, 2022;Jedynak and Charmas, 2021;Wiśniewska et al, 2022;Szczęśniak et al, 2020;Skubiszewska-Zięba et al, 2017;Gusiatin et al, 2023).…”
Section: Introductionmentioning
confidence: 99%